2002
DOI: 10.1046/j.1365-2427.2002.00929.x
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive success of the rotifer Brachionus calyciflorus feeding on ciliates and flagellates of different trophic modes

Abstract: SUMMARY 1. The nutritional value of the bacterivorous ciliate Tetrahymena pyriformis and the algivorous ciliate Coleps sp., as well as the heterotrophic flagellate Chilomonas paramecium and the autotrophic flagellate Cryptomonas ovata, were investigated in population growth experiments using the rotifer B. calyciflorus. The two ciliates, both flagellates, which were of similar size, shape and mobility, were each offered as a sole diet and as a supplement to the alga Monoraphidium minutum, known to support repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 48 publications
(66 reference statements)
3
9
0
1
Order By: Relevance
“…In the present study, these values were lower but, under comparable conditions, were close to 7 days. Similarly, the gross and net reproductive rates observed in our study were lower but within the range documented earlier [26]; the rate of population increase observed here was much closer to that reported earlier (0.32 d Ϫ1 [15]). Much of the data on the life table demography of B. calyciflorus given in the literature is not readily comparable to our work because of the use of different growth conditions in relation to algal species, densities, incubation temperatures and other test conditions.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In the present study, these values were lower but, under comparable conditions, were close to 7 days. Similarly, the gross and net reproductive rates observed in our study were lower but within the range documented earlier [26]; the rate of population increase observed here was much closer to that reported earlier (0.32 d Ϫ1 [15]). Much of the data on the life table demography of B. calyciflorus given in the literature is not readily comparable to our work because of the use of different growth conditions in relation to algal species, densities, incubation temperatures and other test conditions.…”
Section: Discussionsupporting
confidence: 91%
“…This food concentration is well above above the incipient limiting level (ILL ഠ 2.5 μg mL Ϫ1 DW) known for Brachionus [30]. The use of food densities above ILL ensures optimal growth rates [15].…”
Section: Methodsmentioning
confidence: 88%
See 1 more Smart Citation
“…However, it appears that they are not a good source of nutrients. It has been shown that ingesting Paramecium allows predators satisfy their metabolic demands but the carbon input is insufficient to permit adequate reproduction in cladocerans, copepods and rotifers (De Biase et al, 1990;Mohr and Adrian, 2002). The quality of the different diets was reflected in the turbellarian population growth even when the diet consisted only of algae or detritus; this suggests that S. leucops acquires different nutrients, the availability of which, in turn, affects its demographic parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the ciliate metazooplankton link may be very variable when looking at the ciliate species level, but not necessarily on the biochemical level. Generally, although influenced by protists species, algae rather than bacteria seem to be important in providing nutritious food for zooplankton, including the indirect way via ingestion by protozoans (MOHR and ADRIAN, 2002;WEITHOFF and WACKER, 2007).…”
Section: Ecosystem View At Biochemicals In Trophic Interactions In Thmentioning
confidence: 99%